2019
DOI: 10.1111/sji.12746
|View full text |Cite
|
Sign up to set email alerts
|

Two signal half‐century: From negative selection of self‐reactivity to positive selection of near‐self‐reactivity

Abstract: With the emergence of clonal selection ideas in the 1950s, the development of immune cell repertoires was seen to require the negative selection of self‐reacting cells, with surviving cells exhibiting a broad range of specificities. Thus, confronting a universe of not‐self‐antigens, a potential host organism spread its resources widely. In the 1960s, the two signal hypothesis showed how this might work. However, in the 1970s an affinity/avidity model further proposed that anticipating a pathogen strategy of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 51 publications
(90 reference statements)
1
21
0
Order By: Relevance
“…Then, negative selection and deleting all anti–self‐reactivities might allow a niche for survival of pathogens and parasites and would compromise the defensive function of the adaptive immune system. Vrisekoop and Forsdyke suggested that anti‐foreign T cell repertoire might be developed by being initially positively selected on near‐self in order to prevent such avoidance . The dynamic model (with the Integrity hypothesis) presented here is consistent with such a notion.…”
Section: Functional Aspectssupporting
confidence: 79%
See 1 more Smart Citation
“…Then, negative selection and deleting all anti–self‐reactivities might allow a niche for survival of pathogens and parasites and would compromise the defensive function of the adaptive immune system. Vrisekoop and Forsdyke suggested that anti‐foreign T cell repertoire might be developed by being initially positively selected on near‐self in order to prevent such avoidance . The dynamic model (with the Integrity hypothesis) presented here is consistent with such a notion.…”
Section: Functional Aspectssupporting
confidence: 79%
“…This protective (asylum) function of the immune system is arguably more than just tolerance, the latter being perhaps just “careless” non‐reactivity. Asylum would have similar benefits for the host immune defence as the selection of the repertoire on near‐self, proposed recently by Germain group and Forsdyke …”
Section: The Protection By Ttregs (Asylum) Is More Than Tolerancementioning
confidence: 81%
“…That summer, we both left for North America and, sooner or later, both settled in Canada. A half‐century later, we both submitted “two‐signal” retrospectives to the Scandinavian Journal of Immunology …”
Section: Introductionmentioning
confidence: 99%
“…Here my interests included the development of my two‐signal hypothesis, which was different from that of Bretscher and Cohn . In recent times, there have been my personal retrospective in 2012 and my “half‐century” scientific retrospective in 2019 . Having not seen Bretscher's retrospective, I did not cite it in the latter (but I knew it was pending since I had declined a request to review).…”
Section: Introductionmentioning
confidence: 99%
“…6 In subsequent decades, positive selection ideas and their implications for cancer immunotherapy gained general support. 7 It is now recognized that small clones of 'anti-near-self' immune cells exist in patients and can be subject to extracorporeal expansion under tissue culture conditions prior to their return to the same patient. Specific anti-near-self T cell clones should be expandable extracorporeally in quantities that, when reintroduced, would suffice to target autologous cancer cells-a process that has become known as adoptive T cell transfer (ACT).…”
mentioning
confidence: 99%